Measurement tools used to assess interprofessional education and collaborative practice in health professional students: A COSMIN systematic and psychometric review - Anastasia Anna; Ying-Chin Liao; Linlin Lindayani; Aan Nuraeni (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Interprofessional education and collaborative practice (IPE/IPC) are essential for preparing students to work together and respect the unique qualities and abilities of professionals. However, IPE/IPC and its related concepts are highly abstract phenomena and complicated to assess and measure. In consequence, a critical appraisal is needed to evaluate the quality of the instruments. Purpose: This study aimed to critically appraise, compare and summarize the quality of measurement properties of all self-report collaboration questionnaires for health professional students and to provide evidence concerning the psychometric properties of the measurement. Methods: A psychometric review was employed, and the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) approach was applied to assess the methodological quality of the nature of the measurements. Data search using keywords: health professional students, interprofessional, collaboration, teamwork, collaborative, through MEDLINE, EMBASE, and EBSCO-hosted Education Resource Information Centre databases. Results: Seven instruments from 10 reviewed studies were identified. Among them, four instruments targeted attitudes toward collaboration. One instrument focused on students' collaborative learning readiness and had been tested in Hong Kong using English, in Iran using Persian, and in Indonesia using Bahasa Indonesia. One instrument measured perception about IPE, and two studies measured IPE/IPC competencies related to patient-centered, team-based, and collaborative care. The methodological quality assessment indicated that several instruments were less rigorously developed and validated than COSMIN and Quality Criteria of Measurement Properties recommend. Conclusions: The findings of this psychometric review are that the Interprofessional Attitudes Scale is an instrument with adequate content validation and very good structural validity, internal consistency, cross-cultural validity, reliability, measurement error, and criterion validity. It is recommended that the Interprofessional Attitudes Scale be used to measure the interprofessional attitudes of health professional students.